The Effect of Financial Slack on Firm Performance with Lender’s Monitoring as a Moderating Variable - Luthfiani Hamzah Oke; Tanzil Nanny Dewi; Yusi Sari Prima (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study investigates the effect of financial slack on corporate financial performance, by exploring the role of lender’s monitoring as a moderating variable. Using a quantitative approach and moderated regression analysis, data were collected from 273 non-financial companies listed on the Indonesia Stock Exchange in 2023. The study offers a theoretical contribution by testing the validity of agency theory in an emerging market context such as Indonesia, as well as a practical contribution in evaluating the effectiveness of creditor oversight as a managerial control tool over financial slack. Empirical results show that financial slack has a significantly negative effect on financial performance (ROA), indicating potential managerial dysfunction due to excess liquidity. Meanwhile, lender’s monitoring does not show a statistically significant moderating effect. This study highlights the limitations of external monitoring effectiveness in emerging markets and underscores the importance of adaptive and disciplined financial governance in managing slack resources.